Coalition theory: a veto players' approach. (24th September 2013) - Tsebelis, George; Ha, Eunyoung
<x content-type="archive" xml:space="preserve">Abstract</x> Coalition theories have produced arguments about the importance of party positions for participation in government coalitions, but have not connected the existing government institutions (in particular agenda setting) with the coalition government that will be formed. This article presents a veto players' approach to coalition formation, which pushes the logic of non-cooperative game-theoretic models one step further: we argue that policy positions play a significant role in coalition formation because governments in parliamentary systems control the agenda of the policymaking process. As a result, the institutions that regulate this policymaking process affect coalition formation. In particular, positional advantages that a government may have (central policy position of formateur, fewer parties, and small policy distances among coalition partners) will become more necessary as a government has fewer institutional agenda setting advantages at its disposal. The empirical tests presented in this paper corroborate these expectations by explicitly accounting for the conditional effects of policy positions and institutional agenda setting rules on one another in a set of multilevel logit models.